LEGAL CAPACITY AND AGE STANDARDS FOR NASAB GUARDIANS IN INDONESIAN MARRIAGE LAW - Paputungan, Sugiarto; Su’adah, Fatkhiyatus (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2025)
Abstract: Marriage guardianship is a key pillar in the marriage contract that must be fulfilled. According to the Minister of Religious Affairs Regulation No. 20 of 2019, guardianship is classified into nasab (lineal descent) guardians and judicial guardians. The requirement of puberty (baligh) for nasab guardians is considered problematic, as it does not align with Indonesia’s legal definition of adulthood, which sets adulthood at 18 or 21 years depending on the context. This research uses qualitative methods with a normative-juridical approach, based on primary legal documents and secondary references from books and scholarly articles. The study concludes that the puberty requirement, as stipulated in Article 12 Paragraph (2) of PMA No. 20/2019, contradicts the principle of lex superior derogat legi inferiori, the provisions of legal capacity under private law, and the requirement for legal competence.